Desmopressin treatment improves platelet function under flow in patients with postoperative bleeding. (11th June 2015) - Swieringa, F.; Lancé, M. D.; Fuchs, B.; Feijge, M. A. H.; Solecka, B. A.; Verheijen, L. P. J.; Hughes, K. R.; van Oerle, R.; Deckmyn, H.; Kannicht, C.; Heemskerk, J. W. M.; van der Meijden, P. E. J.
Summary Background Patients undergoing major cardiothoracic surgery are subjected to dilution, owing to massive fluid infusion and blood component transfusion. These patients may experience bleeding perioperatively, and are frequently treated with the endothelium‐activating agent desmopressin. Objectives To investigate the effect of desmopressin administration on von Willebrand factor (VWF)‐dependent coagulant and platelet functions under flow conditions. Patients/methods Blood from 16 patients with postoperative bleeding was obtained before and after desmopressin treatment (0.3 μg kg−1 body weight), and assessed for coagulant properties and platelet function. Furthermore, VWF antigen levels and multimer composition were determined in both samples. Results Desmopressin treatment did not change thrombin generation in plasma or whole blood thromboelasticity. Also coagulation factor levels (other than factor VIII) and coagulation times were unchanged, suggesting that desmopressin treatment did not have a major effect on the coagulant activity. On the other hand, desmopressin treatment raised the already high plasma levels of VWF from a median of 116 IU mL−1 (interquartile range [IQR] 102–154 IU mL−1) to a median of 160 IU mL−1 (IQR 126–187 IU mL−1) (P = 0.007), owing to accumulation of the high molecular weight VWF multimers. Furthermore, desmopressin treatment caused an increase in collagen‐dependent thrombus formation and platelet phosphatidylserine exposure. Markers of thrombus formation correlated with the plasma levels of VWF. In vitro control experiments confirmed a major contribution of VWF to thrombus formation and procoagulant activity under conditions of blood dilution. Conclusions Desmopressin treatment of patients with bleeding complications after cardiothoracic surgery induces the release of high molecular weight VWF multimers, which enhance platelet activation and thrombus formation under flow conditions.